Crawford's Fairy Tales - Godard, Barbara (Studies in Canadian Literature, 1979)
Isabella Valancy Crawford's Fairy Tales are a part of the Victorian literary tradition of self-exploration through the fold and childhood traditions of fairy tales. Analysis of fairy tales by anthropologists and folklorists have concerned themselves with recording processes of transmission and clarifying original meanings; through examining Crawford's stories in relation to typical deviations from the norm, provides the reader with a key to the meaning of the stories. In her tales and fables, Crawford draws on East Indian and Native American influences and focusses on love, allegory, and the union of opposites.